2005
DOI: 10.1213/01.ane.0000146433.84742.3a
|View full text |Cite
|
Sign up to set email alerts
|

The Perioperative Management of a Patient with Complex Single Ventricle Physiology and Pheochromocytoma

Abstract: Pheochromocytoma is associated with intense physiologic effects of alpha- and beta-adrenergic stimulation from catecholamine secretion. Perioperative management for these patients includes alpha-adrenergic receptor blockade, intravascular volume replacement, and, if necessary, beta-adrenergic receptor blockade. Significant perioperative changes in preload and afterload, fluid status, heart rate and rhythm, and inotropy can occur and may be contrary to anesthetic management goals for patients with certain condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 12 publications
1
15
0
2
Order By: Relevance
“…Although catecholamine release can have dramatic consequences in patients with Fontan physiology, the anesthetic considerations during pheochromocytoma resection are the same as in other patients. [2][3][4][5][6][7][8][9][10] The general management in our patient followed the principles discussed in previous reports, but a few aspects warrant special attention.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Although catecholamine release can have dramatic consequences in patients with Fontan physiology, the anesthetic considerations during pheochromocytoma resection are the same as in other patients. [2][3][4][5][6][7][8][9][10] The general management in our patient followed the principles discussed in previous reports, but a few aspects warrant special attention.…”
Section: Discussionmentioning
confidence: 53%
“…[5][6][7][8] Tjeuw et al reported a case of an 11-yr-old girl with a single ventricle whose symptoms had been palliated with a Blalock-Taussig shunt. 5 Subsequent reports included a case of a 27-yr-old woman with a right-sided Glenn anastomosis and a central aortopulmonary shunt, 6 a 24-yr-old man with a modified Fontan repair, 7 and a 13-yr-old boy whose symptoms were palliated with a Glenn anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anestezi indüksiyonu, orofaringeal entübasyon ve perioperatif dönemde katekolamin salgılanmasıyla oluşabilecek hipertansiyon yönetimi için; Nikardipine (kalsiyum kanal blokeri), esmolol (β bloker), fentolamine, sodyum nitroprussid, fenoldopam, remifentanil, magnezyum sülfat ve nadiren de adenozin veya prostoglandin E1 gibi kısa etkili ajanlar tercih edilmektedir (4,7,8). Remifentanil adrenokortikal tümör rezeksiyonu yapılan hastada entübasyona ve cerrahi insizyona stres yanıtı önleyebilmesine ve hemodinamik stabiliteyi sağlayabilmesine rağmen, anestezi indüksiyonu sonrasında belirgin kardiyovasküler depresyonla ilgilidir ve feokromasitomalı hastalarda tümör manipülasyonu sırasında katekolamin seviyelerinde artış ile ilişkili hemodinamik değişiklikleri önlemede yetersizdir (8).…”
Section: Discussionunclassified
“…The associations between TBX5, SALL4, and SDH mutations have not been described. However, pheochromocytoma has been reported in patients with various other cyanotic heart diseases such as Fallot complex, single ventricle physiology, and tricuspid atresia [17,18]. Furthermore, a significant correlation between chronic hypoxia and peripheral neuroblastic tumors, including pheochromocytoma, has also been reported [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%